Financial management : principles and applications - Titman, Sheridan (Boston, Massachusetts : Prentice-Hall, 2012)
Financial Management: Principles and Applications gives students a big picture perspective of finance and how it is important in their personal and professional lives.
Part 1. Introduction to Financial Management -- part 2. Valuation of Financial Assets -- Part 3. Capital Budgeting -- Part 4. Capital Structure and Dividend Policy -- Part 5. Liquidity Management and Special Topics in Finance .
Includes index.
Keywords: FINANCIAL MANAGEMENT